Answer:
2212$
Step-by-step explanation:
Answer:
<h2>(f · g)(x) is odd</h2><h2>(g · g)(x) is even</h2>
Step-by-step explanation:
If f(x) is even, then f(-x) = f(x).
If g(x) is odd, then g(-x) = -g(x).
(f · g)(x) = f(x) · g(x)
Check:
(f · g)(-x) = f(-x) · g(-x) = f(x) · [-g(x)] = -[f(x) · g(x)] = -(f · g)(x)
(f · g)(-x) = -(f · g)(x) - odd
(g · g)(x) = g(x) · g(x)
Check:
(g · g)(-x) = g(-x) · g(-x) = [-g(x)] · [-g(x)] = g(x) · g(x) = (g · g)(x)
(g · g)(-x) = (g · g)(x) - even
Answer:
The answer is,surface area= ✓<u>416</u>
Answer:
me
Step-by-step explanation:
pleas i'm begging you
Answer:
5,976 workers
Step-by-step explanation:
498 times 12 = 5976